Continuum education in nursing: knowledge, activities and barrier found in a school maternity - Davim, Rejane Marie Barbosa; Torres, Gilson de Vasconcelos; Santos, Sérgio Ribeiro dos (Rev Rene, 2000)
This study intends to identify the knowledge and activities from a group of 16 nurses who participated in the Continuing Training Program in the School Maternity Hospital. The main findings showed that the Training Program used importance strategies such as open-discussion and lectures. Also, there were barriers for the continuity of this Program for instance, limited human and material resources, and low acknowledge of the nurse’s career.